Utilization of Matoa Leaf Extract (Pometia pinnata) in the Formulation of Red Bean Ice Cream as an Antioxidant-Rich Snack - Annisa Mayang Soliha; Muhammad Said Ridho; Candra Saka Nusantari (Universitas Airlangga, 2026)
Background: Red bean ice cream is a dairy-based product combined with red beans that is widely known and accepted among various age groups in Indonesia. Its protein and fiber content make this ice cream a potential functional food that may promote a healthy lifestyle and reduce the risk of malnutrition. However, low-temperature processing and storage can significantly reduce antioxidant activity, resulting in relatively low levels of antioxidants. Matoa leaves contain flavonoids and steroids with antimicrobial, antifungal, antioxidant, and anticancer activities. Objectives: This study aimed to assess the antioxidant activity, total phenolic content, and organoleptic acceptability of red bean ice cream supplemented with matoa leaf extract. Methods: This study employed an experimental approach using a Completely Randomized Design (CRD). Statistical analyses included one-way analysis of variance (ANOVA), antioxidant activity analysis using the DPPH method, and total phenolic content analysis using the Folin–Ciocalteu method. Organoleptic assessment was conducted using a hedonic test involving 30 semi-trained panelists. Furthermore, the estimated nutritional values were determined using the 2017 Indonesian Food Composition Table (TKPI). Results: The findings demonstrated a significant increase in the antioxidant activity and total phenolic content (p<0.05). Formula F1 was the most favored formulation, although the addition of matoa leaf extract did not significantly influence the organoleptic acceptability. Conclusion: The utilization of Matoa leaf extract has the potential to enhance the quality of functional foods without compromising their sensory properties.